Efeitos da TENS nos sintomas eméticos e seus desfechos em mulheres com câncer de mama durante a quimioterapia - Santos, Luana Farias dos (2019)
Introduction: For the 2018-2019 biennium, approximately 59,700 new cases of breast Cancer (CA) are expected each year. Among the therapies employed for the treatment of CA is chemotherapy (QT), a technique that has been shown to be effective in the management of this disease by attacking cancer cells. However, it can lead to numerous adverse reactions, including nausea and vomiting (N/V), fatigue and reduced Quality of Life (QL). Thus, the investigation of the use of Transcutaneous Electrical Stimulation (TENS) in chemotherapy-induced symptoms in women with breast CA, while complementing the exercise of the physical therapist could be a tool in improving the health problems of this population, since the fear by treatment and its side effects even contributes to its abandonment, reducing the chances of therapeutic success. Objective: To evaluate the repercussions of TENS applied at the acupuncture point PC6 on N/V modulation and its implications on fatigue and QL in women with breast CA during chemotherapy treatment. Method: We evaluated women from 35 to 65 years old, diagnosed with breast CA, who were in attendance at the QT outpatient clinic of the Santa Maria University Hospital, using a sociodemographic questionnaire, a Multinational N/V incidence questionnaire. Association of Supportive Care in Cancer Antiemesis Tool (MAT), quality of life of the European Organization for Research and Treatment of Cancer Quality of Life Supplementary Questionnaire (QLQ - C30) and fatigue the Functional Assessment of Cancer Therapy Fatigue (FACT-F). After the initial evaluation, the volunteers were randomized through opaque and sealed envelopes to compose the Placebo Group (GP), which received the placebo intervention (the device remained off) or to the TENS Group (GT), in which the patients received the placebo. TENS treatment during the QT period. The study was blinded being a therapist for the application of the TENS protocol and another researcher for the collection procedures. TENS, Neurodyn Portable TENS model of Ibramed brand, was applied before infusion of chemotherapeutic drugs for 30 minutes at acupuncture point PC6 with frequency of 10Hz and 150us. Women underwent a single application of TENS before each QT cycle and questionnaires administered before each intervention. The MAT questionnaire was also applied by telephone contact at 24h and 48h post QT. Results: We evaluated 31 women, 16 in the GP and 15 in the GT. The groups were homogeneous regarding sociodemographic and medical treatment variables. Regarding the pre, 24h and 48h post-QT emetic symptoms, a difference was observed between the groups regarding the presence of nausea in the last 24h at 24h and 48h post- QT only in Cycle 2 for the GP. Regarding the variables Fatigue and QL, no difference was observed between the groups during the entire QT. Conclusion: TENS does not appear to be an eligible therapy for N/V reduction, fatigue and QL control during the period of high emetogenic QT.